Students’ Environmental Decision-Making in Secondary Biology Education: A Bibliometric Analysis and Systematic Literature Review - Vyna Rohmatika; Kusnadi Kusnadi; Bambang Supriatno (Journal of General Education and Humanities, 2026)
Decision-making skills on environmental issues are a key 21st-century competency that should be systematically fostered through biology learning. However, research on this topic remains fragmented across educational contexts, learning approaches, and research designs, limiting a comprehensive understanding of publication trends, effective interventions, and research gaps. This study aimed to map research trends, identify learning interventions that enhance students' decision-making skills, and reveal thematic, methodological, and contextual gaps. A mixed review approach combining bibliometric analysis and a systematic literature review (SLR) was employed. The bibliometric analysis examined 414 Scopus-indexed publications from 2005–2025, while the SLR synthesized 11 eligible empirical studies. Bibliometric data were processed using OpenRefine and analyzed with VOSviewer and Biblioshiny, whereas the selected studies were narratively synthesized based on intervention type, research design, outcomes, and thematic coding of reported limitations and future research directions. The findings reveal a steady increase in publications over the past two decades, indicating growing scholarly interest in environmental decision-making. The reviewed studies suggest that socioscientific issues, open inquiry, role-play, and explicit decision-making frameworks, such as OIDDE and the Four Component Model, can improve evidence-based reasoning, value consideration, and environmental responsibility. However, variations in research designs, interventions, assessment instruments, and outcome measures limit comparisons across studies. Key research gaps include the limited development of comprehensive assessment instruments, the scarcity of longitudinal studies, and insufficient investigation of local educational contexts. These findings provide directions for future research and practical implications for developing biology curricula and environmental education that strengthen students' informed and responsible decision-making skills.